7-(5-3x)=5x+6

Simple and best practice solution for 7-(5-3x)=5x+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7-(5-3x)=5x+6 equation:


Simplifying
7 + -1(5 + -3x) = 5x + 6
7 + (5 * -1 + -3x * -1) = 5x + 6
7 + (-5 + 3x) = 5x + 6

Combine like terms: 7 + -5 = 2
2 + 3x = 5x + 6

Reorder the terms:
2 + 3x = 6 + 5x

Solving
2 + 3x = 6 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
2 + 3x + -5x = 6 + 5x + -5x

Combine like terms: 3x + -5x = -2x
2 + -2x = 6 + 5x + -5x

Combine like terms: 5x + -5x = 0
2 + -2x = 6 + 0
2 + -2x = 6

Add '-2' to each side of the equation.
2 + -2 + -2x = 6 + -2

Combine like terms: 2 + -2 = 0
0 + -2x = 6 + -2
-2x = 6 + -2

Combine like terms: 6 + -2 = 4
-2x = 4

Divide each side by '-2'.
x = -2

Simplifying
x = -2

See similar equations:

| 3x^2+4x-13y+3xy=21 | | 1-4x=31 | | 3s-5s+s-6s= | | 14+2x-9=3x-8 | | 4b-5=68.96 | | (2g-2)=(4g-9) | | 5x-(-8)=28 | | y=ab+z | | 60+28n=38n | | 7v-(6-2v)=1 | | 55.2+-7.5k=-15.3 | | y=-7/5x-3 | | -4x-10x=56 | | B-2b/0-a | | -zx+y=-5 | | -2x+.2=1.8 | | 84-x=3x | | 1.2x+4.3=2.1+-1x | | 3/8x=-4 | | 0=50x^2-62x | | x^4+7x+6=0 | | 8x+9=9x-2 | | 49x^2/3-x^1/3-6=0 | | 6x+1=4x+39 | | x^2+1807x-4200=0 | | y+-.3y= | | (5z+4)(1-z)=0 | | 12xy+28x+15y+35=0 | | 7x-4=5+6x | | (x+6)(x+2)-[x(x-2)]=132 | | 8x+5=10+5x | | x+2=-42+5x |

Equations solver categories